Corporate fraud exposed : a comprehensive and holistic approach - Baker, H. Kent; Purda, Lynnette; Saadi, Samir (Emerald Publishing Limited, 2020)
After each major corporate scandal, new suggestions for combatting fraud emerge from regulators and industry professionals. Despite changes to guidelines for firms' corporate governance, augmented protection for whistle blowers, and enhanced cybersecurity measures, evidence documents an alarming increase in the prevalence and severity of corporate fraud. The rapidly changing laws aimed at curbing corporate fraud sometimes lag behind the changing sophistication of fraud schemes. Corporate Fraud Exposed discusses the motivations and drivers of fraud including agency theory, executive compensation, and organizational culture. It examines fraud's consequences for various firm stakeholders and its spillover effects to other corporations, the political environment, and financial market participants, including those who participate via crowdfunding platforms. This book provides a fresh look at this intriguing but often complex subject. It skillfully blends the contributions of a global array of scholars and practitioners into a single review of some of the most important topics in this area. Given its broad scope, this practical and comprehensive title should be of interest to anyone curious about corporate fraud.